Case-Control Study Examining the Association between Selective Serotonin Reuptake Inhibitors Use and Hepatocellular Carcinoma - Lai, Shih-Wei; Liao, Kuan-Fu; Lin, Cheng-Li; Lin, Hsien-Feng (Frontiers in Pharmacology, 2017)
Objectives. The aim of the study was to explore the relationship between selective serotonin reuptake inhibitors use and hepatocellular carcinoma in Taiwan. Methods. Using the database of the Taiwan National Health Insurance Program, we conducted a population-based case-control study to identify 4901 subjects aged 20 years or older with newly diagnosed hepatocellular carcinoma in 2000-2013 as the cases. We randomly selected 19604 subjects aged 20 years or older without hepatocellular carcinoma as the controls. Both cases and controls were matched with sex and age. Ever use of selective serotonin reuptake inhibitors was defined as a subject who had at least a prescription for selective serotonin reuptake inhibitors before index date. Never use was defined as a subject who never had a prescription for selective serotonin reuptake inhibitors before index date. The odds ratio (OR) and 95% confidence interval (CI) for hepatocellular carcinoma associated with selective serotonin reuptake inhibitors use was estimated by the multivariable logistic regression model. Results. Among subjects with any one of the comorbid conditions associated with for hepatocellular carcinoma, the adjusted OR of hepatocellular carcinoma was 0.89 (95% CI 0.75, 1.06) for subjects with ever use of selective serotonin reuptake inhibitors, comparing with never use. Conclusion. The findings indicate that among subjects with any one of the comorbid conditions associated with hepatocellular carcinoma, no significant association can be detected between selective serotonin reuptake inhibitors use and hepatocellular carcinoma.